2018
DOI: 10.1136/bmjopen-2017-020475
|View full text |Cite
|
Sign up to set email alerts
|

Digital breast tomosynthesis plus synthesised images versus standard full-field digital mammography in population-based screening (TOSYMA): protocol of a randomised controlled trial

Abstract: IntroductionDevelopment of digital breast tomosynthesis (DBT) provides a technology that generates three-dimensional data sets, thus reducing the pitfalls of overlapping breast tissue. Observational studies suggest that the combination of two-dimensional (2D) digital mammography and DBT increases diagnostic accuracy. However, because of duplicate exposure, this comes at the cost of an augmented radiation dose. This undesired adverse impact can be avoided by using synthesised 2D images reconstructed from the DB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
0
10
0
7
Order By: Relevance
“…Retrospective trials have shown similar results with no statistically significant differences between interval cancer rates (13,14). To our knowledge, randomized controlled screening trials of DBT with interval cancer rates as end point have not yet published such data (15)(16)(17). In general, interval cancers are more aggressive than screen-detected cancers because they are similar to symptomatic breast cancer in women who are not screened (18).…”
mentioning
confidence: 87%
“…Retrospective trials have shown similar results with no statistically significant differences between interval cancer rates (13,14). To our knowledge, randomized controlled screening trials of DBT with interval cancer rates as end point have not yet published such data (15)(16)(17). In general, interval cancers are more aggressive than screen-detected cancers because they are similar to symptomatic breast cancer in women who are not screened (18).…”
mentioning
confidence: 87%
“…Evidence before this study To address the knowledge gap about interval breast cancer rates for DBT versus mammography screening, and to plan an individual participant data (IPD) meta-analysis, we searched the literature in July 2016 to identify prospective studies that investigated DBT screening and reported data on cancer detection and (potentially) interval cancer data at follow-up; four non-randomised prospective studies met eligibility criteria for our proposed study. Since our initial literature search (using an updated search April 2020) two studies have reported that at follow-up of DBT screening participants Bernardi 2020) there was no significant difference in interval cancer rates between DBT and mammography screening, and two randomised trials (Weigel 2018;Pattacini 2018) have indicated that interval cancer rates will be reported as part of trial outcomes.…”
Section: Research In Contextmentioning
confidence: 99%
“…Another important ongoing clinical trial in this topic is called Digital Breast Tomosynthesis plus Synthesised Images versus Standard Full-Field Digital Mammography in Population-Based Screening (TOSYMA), which is being carried out in Germany. The authors aim to include 80,000 women aged 50 to 69 years who are attending their routine mammography screening programme 73 . The primary endpoints are the detection rate of invasive breast cancers during screening examinations and the cumulative incidence of interval cancers in the two years after a negative examination.…”
Section: Positive Predictive Value and False Positive Recallsmentioning
confidence: 99%